Who is Copying Who? Similarities of Words between Bahasa Melayu and Maranao: An Ethnographic Study - Sohayle M. Hadji Abdul Racman; Monaimah Gubat-Manabilang Gubat-Manabilang; Grace S. Rafal; Anisalam S. Magomnang (Journal of Communication and Cultural Trends, 2022)
This research came to its realization during my PhD studies in Brunei Darussalam. Since the past decade, it has been theorized that the Malay language of Nusantara region, now Malaysia, Indonesia, Borneo, Philippines, Singapore, Southern Thailand and other Southeast Asian nations originated from the Austronesian (Malayo-Polynesian) language family. The Malay language is spoken by the Malays in Southeast Asia. However, due to the sporadic nature of Southeast Asia consisting of chains of numerous islands and islets, the Malay language has developed and evolved across various localities, islands, and regions. In Philippines alone, there are 7, 641 islands and islets and the country is home to more than 150 languages, which all evolved from the Austronesian (Malayo-Polynesian) language family. The Maranao language is one of the major languages of the Philippines. Maranao is the lingua franca of the Maranaos in Mindanao island. Whereas, Bahasa Melayu or Malay is the language of the Malays in Brunei Darussalam. To pave the pace with the agenda of the research, the research was carried out using ethnography as a research method to find out the similar words between the Maranao language and Bahasa Melayu. Geographically, Brunei Darussalam is strategically closer to Mindanao, Philippines.Keywords: Bahasa Melayu, Brunians, ethnographic research, Maranao language, Malay